COMPUTER MODELLING OF PROCESSES FHASE OF FORMATIONS IN SYSTEM NI-AL WITH CONCENTRATION of the COMPONENTS CORRESPONDING TO PHASES NI3AL AND NIAL - Denisova, N.F.; Starostenkov, M.D.; Skakov, M.K. (Recent Contributions to Physics, 2008)
Real world is devoted to the research of the process of self developing high- temperatures syntheses of 2D crystals by the method of molecules dynamic. We use pure Ni as a matrix crystale with the nano- fraction of Al in the form of ideal symmetrical six- cornered figures of different sieges based in the centre of the block. As a result of the computer experiment was got the dependent of temperature of the beginning of the atom- exchanging process from the sieges of Al fraction.